PAT-6 Brain Histopathology of Cynomolgus Monkey (Macacafascicularis) with Memory Impairment Indicated by Alzheimer Type Neurodegenerative Disease - Vinka Aftinata Kusumaputri; Huda Shalahudin Darusman; Dewi Ratih Agungpriyono (Hemera Zoa, 2018)
The study is about the degenerative lesion found in nine cynomolgus monkeys that showed decline cognitive function during theirold age life. In previous studies, the brain of these cynomolgus monkeys has been tested positive for amyloid deposits by using the ELISA test.